Correlation analysis of serum FGLP1, UACR and the risk of heart failure in patients with type 2 diabetes: Serum FGLP1, UACR and the risk of heart failure in T2D - Xia, Lianheng; Guo, Yingshuo; Wang, Jiaxin; Wang, Tingxuan; Xu, Chunhui; Song, Meiyu; Du, Chang; Wang, Qingjie; Gao, Jie (Journal of Medical Biochemistry, 2026)
Objective To explore the correlations between serum FGLP1 (Fibrinogen-like protein 1 C-terminal peptide) levels, the urine albumin-to-creatinine ratio (UACR) and left ventricular diastolic dysfunction (LVDD) in elderly patients with type 2 diabetes mellitus (T2DM). Methods From August 2023 to August 2025, 256 elderly patients with T2DM who were admitted to our hospital were selected as the case group, and 120 healthy individuals who underwent physical examinations were selected as the control group. In accordance with the diagnostic criteria for LVDD, T2DM patients were divided into a disorder group (n=70) and a nondisorder group (n=186), and single-factor analysis, multivariate logistic regression analysis, and Spearman correlation analysis were performed to explore the correlation between serum FGLP1 levels, UACRs and LVDD in T2DM patients, and receiver operating characteristic curves were used to evaluate the ability of serum FGLP1 levels and urine UACR to predict LVDD. Results The serum FGLP1 concentration and urine UACR were higher in the case group than in the healthy group (P<0.05). There were statistically significant differences in age, disease duration, serum FGLP1 concentration and UACR between the LVDD group and the non-LVDD group (P<0.05). Multivariate logistic regression analysis revealed that age ≥ 75 years, long disease duration, elevated UACR, and elevated serum FGLP1 concentration were independent risk factors for LVDD in patients with T2DM (P<0.05). Spearman correlation analysis indicated a positive association between LVDD and serum FGLP1 levels as well as UACR (r = 0.551, 0.559; both P<0.05). The areas under the curve for predicting LVDD by serum FGLP1 concentration, urine UACR and the prediction model were 0.848, 0.896 and 0.956, respectively. Conclusion Serum FGLP1 levels and urinary UACR in elderly patients with type 2 diabetes mellitus are closely related to LVDD. The combined detection of these two indicators is helpful for the early diagnosis of LVDD.